Biosensing with DNAzymes. (6th July 2021) - McConnell, Erin M.; Cozma, Ioana; Mou, Quanbing; Brennan, John D.; Lu, Yi; Li, Yingfu
Abstract : This article provides a comprehensive review of biosensing with DNAzymes, providing an overview of different sensing applications while highlighting major progress and seminal contributions to the field of portable biosensor devices and point-of-care diagnostics. Abstract : This article provides a comprehensive review of biosensing with DNAzymes, providing an overview of different sensing applications while highlighting major progress and seminal contributions to the field of portable biosensor devices and point-of-care diagnostics. Specifically, the field of functional nucleic acids is introduced, with a specific focus on DNAzymes. The incorporation of DNAzymes into bioassays is then described, followed by a detailed overview of recent advances in the development of in vivo sensing platforms and portable sensors incorporating DNAzymes for molecular recognition. Finally, a critical perspective on the field, and a summary of where DNAzyme-based devices may make the biggest impact are provided.